Composition and application of extremely-ultrahigh-temperature-resistant cement paste system material suitable for low-medium-temperature well cementation environment

By introducing aluminum, silicon and phosphorus elements into the cementing cement slurry and combining specific admixtures to form an extremely ultra-high temperature cement slurry system, the problem of existing cement slurry failure at extremely high temperatures is solved, and efficient cementing and long-term stability in low and medium temperature environments are achieved.

CN119822761APending Publication Date: 2025-04-15CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510018666.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing cementing cement slurry system fails under extreme high temperature environments and cannot meet the high-temperature durability requirements of unconventional shallow well mining.

Method used

The large-scale introduction of aluminum, silicon and phosphorus elements in a certain proportion is adopted to form a special calcium aluminate hydrate, calcium silicate hydrate and calcium phosphate hydrate. Combined with high-temperature strength stabilizers, retarders, water loss-reducing agents, toughening materials, drag-reducing agents and defoaming agents, an extreme-resistant ultra-high temperature cementing system suitable for low and medium-temperature cementing environments.

Benefits of technology

It achieves rapid hydration at low temperature to form high early strength, and maintains long-term strength stability in high temperature environments, reducing the strength decline of cement stones, and improving the durability and high-temperature resistance of cementing cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230668460000141
    Figure BDA0005230668460000141
  • Figure BDA0005230668460000151
    Figure BDA0005230668460000151
  • Figure BDA0005230668460000171
    Figure BDA0005230668460000171
Patent Text Reader

Abstract

The invention relates to composition and application of an extreme ultra-high temperature resistant cement paste system material suitable for a low-medium temperature well cementation environment, and the extreme ultra-high temperature resistant cement paste system material comprises the following components in parts by weight: 100 parts of an extreme ultra-high temperature resistant cement cementing material, 25-33 parts of a high temperature resistant strength stabilizer, 2-8 parts of a retarder, 6-10 parts of a fluid loss agent and 0.4-1.0 part of a toughening material, 1.0-1.8 parts of a drag reducer, 3-6 parts of a defoaming agent and 35-48 parts of water. The invention provides an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature well cementation environments and a matched additive thereof, and aims at rapid pumping of well cementation cement slurry cement of an unconventional shallow well in special resource opening modes such as shallow heavy oil steam huff and puff and in-situ combustion, shale oil in-situ conversion and coal underground gasification. According to the present invention, the special requirements of low-temperature formation strength and extreme high-temperature operation resistance are met, the problems of long well cementation cement reaction time, low early strength, later strength reversion, low strength at high temperature and cracking are solved, the low-temperature early strength and high-temperature resistance characteristics are provided, and the reliable, effective and targeted cement slurry well cementation system is provided for the extreme high-temperature shallow well cementation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cementing of unconventional shallow wells, and in particular to a material composition and application of an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments, and is suitable for various resource development methods such as steam stimulation or fire burning of shallow heavy oil, in-situ conversion of shale oil, and shallow coal underground gasification. Background Art

[0002] my country has huge reserves of heavy oil resources, with land and ocean heavy oil accounting for 27% and 65% of the total oil and gas resources respectively, mainly distributed in North China, Northeast China and Bohai Bay. Compared with foreign countries, my country's heavy oil resources are more difficult to exploit. At present, thermal recovery technology is widely used in heavy oil exploitation due to its advantages such as simple operation, among which steam huff and puff, steam drive and oil layer burning are the representatives of thermal recovery technology.

[0003] Coal gasification and shale oil are the key to future energy development. The improvement of oil well technology is the premise of energy extraction. Among them, cementing technology is the key to oil well production safety. The quality of cementing largely determines the service life of oil and gas wells and is the fundamental guarantee for generating benefits. Heavy oil is generally not buried deep, mostly in the range of 150 to 2000m, and the formation temperature is between 20 and 60℃. At such a depth, the formation is relatively loose and has a large well diameter expansion rate. At the same time, under low temperature conditions underground, ordinary G-grade silicate cement is used for cementing. The cement slurry hydration speed is slow and cannot form a large early strength. There are technical risks such as gas and water channeling and poor cement ring bonding quality. In shallow thermal recovery wells of unconventional oil and gas, the temperature is generally above 300°C during steam extraction, and even reaches 600-700°C when the oil layer is burned. The temperature of in-situ conversion of shale oil and underground coal gasification reaches 1000°C, which forms a huge contrast with the low temperature during cementing. Under high temperature, the porosity of cement stone increases, the overall structure becomes loose, and the mechanical strength drops sharply. Therefore, whether the cementing cement stone can withstand such high temperature and maintain a certain durability is a technical difficulty in cementing shallow thermal recovery wells of unconventional oil and gas.

[0004] For ordinary G-grade silicate cement system, the volume of cement stone expands due to the high temperature of thermal recovery, and the CSH gel is completely decomposed, completely losing the cementing effect. Therefore, silicate cement should not be used in situations involving thermal cycles. Combined with the cementing characteristics of unconventional shallow wells such as shallow heavy oil, coal gasification, and hot dry rock: rapid pumping, strength formation at low temperature, and high temperature resistance, we should try to introduce a non-silicate cement slurry system to form a new high-temperature resistant cement slurry system.

[0005] The Chinese patent with publication number CN110105030A discloses a cementing material suitable for low temperature environment and its production method, the formula of which is mainly composed of the following raw materials (mass percentage): 75-89% of silicate cement clinker, 1-8% of sulphoaluminate cement clinker, 1-8% of high-alumina cement clinker, 2-4% of dihydrate gypsum, 0.5-1.2% of dispersant, and 1-4% of retarder. The invention uses silicate cement as the main body and is combined with sulphoaluminate cement. On the basis of early strength, it alleviates the strength decline problem of cement stone to a certain extent, but does not involve the high temperature resistance of cement stone. It is difficult to control the thickening time when sulphoaluminate cement is mixed with silicate cement.

[0006] The Chinese patent with the publication number CN114477876A discloses a long-term high temperature resistant, toughened cementing sand cement composite material and a preparation method. The long-term high temperature resistant, toughened cementing sand cement composite material is composed of a solid component and a liquid component; the solid component is composed of 40-60% cement, 3-8% alumina, 30-50% ultrafine high purity silica sand, 1.5-2.1% additives and 2.2-6% toughening materials by weight; the liquid component is composed of 70-73% water, 6-7% nano iron oxide and 20-24% oil well cement admixture by weight. This invention solves the problem of cement stone strength decay, but the test condition is only up to 200°C, and the ultra-high temperature condition of more than 600°C in the process of heavy oil thermal recovery is not considered. The cement stone is easy to crack under ultra-high temperature environment, and the cement thickening of the invention exceeds 5h, which is not suitable for cementing work in unconventional shallow wells.

[0007] The Chinese patent with publication number CN106833567A discloses a high-strength, high-toughness, high-temperature resistant cementing slurry system and its preparation method and design method. Its formula is mainly composed of the following raw materials: 100 parts of oil well cement, 20-25 parts of coarse quartz sand, 15-20 parts of fine quartz sand, 2-10 parts of nano-silicon dioxide, 3.2-8.6 parts of fluid loss reducer, 0.8-2.0 parts of dispersant and 45-70 parts of water. Under the condition of 250°C, the strength of cement paste in this invention exceeds 60MPa, but the curing time is up to 28d, and the long-term strength decline of cement paste is not considered. Like the above patent CN114477876A, the temperature is not raised to above 600°C, the cracking problem of cement paste is not considered, and the initial strength development is slow.

[0008] The Chinese patent with the publication number CN115231869A discloses a 350℃ resistant non-fading heavy oil thermal recovery cement slurry, the formula of which is mainly mixed with the following raw materials: based on 100 parts by weight of the cement, the additives include: 0.5-3 parts by weight of fluid loss reducer, 15-40 parts by weight of heat stabilizer, 20-50 parts by weight of silica powder, 1-5 parts by weight of expansion agent, 0.1-2 parts by weight of defoamer, 0.1-3 parts by weight of retarder, and 0-25 parts by weight of density regulator. The cement stone in the patent is cured in a 60℃ normal pressure curing kettle for 48h, and the cured cement stone is placed in a high temperature and high pressure curing kettle, and the temperature is raised to 350℃ and 21MPa according to the set program, and the condition is maintained for continued curing. After the cement stone is cured at 350℃ for 28d, the maximum strength is 40MPa. The curing temperature is low, and the thickening time of the cement slurry and the stress deformation of the cement stone are not considered, which damages the casing.

[0009] The Chinese patent with publication number CN102994058A discloses a high temperature resistant non-silicate cement slurry system for heavy oil thermal recovery well cementing, wherein the formula is mainly composed of the following raw materials: 100 parts of high temperature resistant cement, 1.0-4.0 parts of fluid loss reducer, 1.0-4.0 parts of dispersant, 0.5-3.0 parts of setting regulator, 60-120 parts of water, and 15-80 parts of heat regulator; the high temperature resistant cement is mixed with component A and component B in a weight ratio of 1:1, and the components The chemical composition of A is composed of the following weight ratios: Al2O3 50-77 parts, SiO2 0.5-8.0 parts, Fe2O3 0.5-2.5 parts, R2O (Na2O + 0.658K2O) 0-0.4 parts; the main minerals of the clinker of component B are composed of the following weight ratios: 3CaO·Al2O3·CaSO4 33-63 parts, 2CaO·SiO2 14-37 parts, 6CaO·Al2O3·2Fe2O3 15-35 parts. The invention of a high-temperature resistant non-silicate cement slurry system for cementing heavy oil thermal recovery wells has a small strength change after multiple rounds of tests at 315°C, but the strength is all lower than 30MPa, which cannot guarantee the quality of cementing. In addition, the water loss of the cement slurry system of the invention exceeds 60mL, which does not meet the API water loss standard, has a short thickening time, is easy to flash, cannot be effectively controlled, and has a large construction risk.

[0010] Through the above patent, the main temperature range of high-temperature resistant cementing cement stone is currently 200℃~315℃, which can be used for steam throughput, but is not fully suitable for unconventional shallow well exploitation methods. The main test objects are the strength and elastic modulus of cementing cement stone after multiple rounds of high-temperature and high-pressure maintenance. No integrity research has been conducted for the special needs of unconventional oil and gas shallow thermal well reservoir exploitation cementing rapid pumping, strength formation at low temperature, and resistance to extreme high temperature operations. Moreover, the current cementing cement slurry is mainly a silicate cement slurry system, which cannot be adapted to extremely high temperature shallow well cementing. Therefore, it is urgent to carry out the research and development of an extreme ultra-high temperature resistant cement slurry and its supporting admixtures to form an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments. Summary of the invention

[0011] The present invention aims to provide an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment, which is combined with the rapid pumping of unconventional shallow well cementing cement for special resource opening methods such as steam throughput of shallow heavy oil and fire oil layer exploitation, in-situ conversion of shale oil, underground coal gasification, etc., to form strength at low temperature and meet the special needs of high temperature resistant operations. The present invention aims to solve the problems existing in the existing cement slurry systems for cementing wells, such as slow strength formation of silicate cement slurry system and weak high temperature resistance, serious strength decline in phosphate aluminate cement and aluminate cement systems in the middle and late stages, less research on supporting admixtures, high engineering application cost and great difficulty. According to the hydration mechanism of the cementing cement slurry system, the presence of silicon can improve the high temperature resistance of cement stone. After hydration, a colloidal calcium silicate hydrate "CSH" is formed, which is a good cementing material under low temperature conditions. Under high temperature conditions, crystal transformation will occur, the strength of cement stone decreases, and the strength of cement stone will shrink under high temperature conditions. The presence of aluminum will increase the hydration rate of the cement system, which has an enhancing effect on the high temperature resistance of cement stone. Therefore, the present invention forms a new cementing cement slurry system, in which aluminum, silicon and phosphorus are introduced in large quantities in a certain proportion, and a special calcium aluminate hydrate, calcium silicate hydrate and calcium phosphate hydrate are formed after hydration. The introduction of aluminum makes the cement slurry system have a faster hydration rate under low temperature conditions, promotes the formation of the above-mentioned special hydrate, and increases the initial strength of cement stone. At the same time, the joint action of aluminum, silicon and phosphorus alleviates the strength shrinkage problem of cement stone under normal temperature and high temperature environments. The present invention also provides a material composition of an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments, and an application-matched high temperature strength stabilizer, retarder, fluid loss reducer, toughening material, drag reducer and defoaming agent, which has the characteristics of low temperature early strength and extreme ultra-high temperature resistance.

[0012] In order to perfectly achieve the above-mentioned invention object, the technical solution of the present invention is as follows:

[0013] The invention discloses a material composition and application of an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments, characterized in that, by weight, the composition ratio of each component is 100 parts of extreme ultra-high temperature resistant cement gelling material, 25 to 33 parts of high temperature strength stabilizer, 2 to 8 parts of retarder, 6 to 10 parts of fluid loss reducer, 0.4 to 1.0 parts of toughening material, 1.0 to 1.8 parts of drag reducer, 0.3 to 0.6 parts of defoaming agent and 35 to 48 parts of water.

[0014] Among them, the extremely high temperature resistant cementitious materials are CaO·Al2O3, 3Al2O3·2SiO2, CaSO4·2H2O, NaAlO2, 2CaO·Al2O3·SiO2, Ca 10 The solid composite obtained by mixing (PO4)6(OH)2 in a mass ratio of 36-42:8-13:23-29:6-10:12-15:8-15 has a fast hydration rate of CaO·Al2O3 in the early stage, which improves the early strength. CaSO4·2H2O and NaAlO2 will promote the formation of hydration products ettringite and hydrated calcium aluminosilicate gel, and promote the strength development of extremely high temperature resistant cementitious materials. Under high temperature environment, 3Al2O3·2SiO2 and 2CaO·Al2O3·SiO2 promote the hydration products to further form structurally stable hydrated calcium aluminum feldspar C2ASH8 and calcium aluminum garnet Ca3Al2(SiO4)3, so that the extremely high temperature resistant cementitious materials maintain long-term strength stability. 10 (PO4)6(OH)2 plays a strong binding role in the hydration process. Cement binder materials maintain stable strength under extreme ultra-high temperature conditions and can reduce the complexation of phosphorus and calcium ions during the hydration process, so that the cement slurry system has better fluidity and reasonable thickening time.

[0015] CaO·Al2O3 is a powdered solid with a mesh size of 50-80 and a purity of more than 98.0%; 3Al2O3·2SiO2 is an industrial-grade solid powder with a particle size of 200-240 mesh and a purity of more than 99.0%; CaSO4·2H2O is an industrial-grade solid powder with a particle size of 325-400 mesh and a purity of more than 99.5%; NaAlO2 is an industrial-grade solid powder with a particle size of 160-240 mesh and a purity of more than 98.5%; 2CaO·Al2O3·SiO2 is an industrial-grade solid powder with a particle size of 200-240 mesh and a purity of more than 99.5%; Ca 10 (PO4)6(OH)2 is an industrial grade solid powder with a particle size of 900-1250 mesh and a purity of more than 99.8%.

[0016] The high temperature strength stabilizer is a solid composition obtained by mixing kaolin and quartz sand in a mass ratio of 17-23:9-14. The high temperature strength stabilizer provides highly active silicon dioxide and aluminum oxide to form aluminosilicate minerals under high temperature conditions and has good high temperature resistance effect.

[0017] Metakaolin is an industrial-grade solid powder with a particle size of 900-1250 mesh and a purity of more than 99.0%; quartz sand is an industrial-grade solid powder with a particle size of 150-240 mesh and a purity of more than 99.5%.

[0018] Kaolin and quartz sand provide highly active silica, wherein the highly active silica reacts with calcium aluminate to form hydrated calcium aluminum feldspar C2ASH8. C2ASH8 is a stable substance, which reduces the generation of metastable hydrated calcium aluminate, thereby inhibiting the conversion of the product and reducing the amount of C3AH6 present.

[0019] C3AH6 belongs to the cubic crystal system and often has many defects, such as dislocations, and the bonding between crystals is poor, which will cause the internal structure of the cement paste to become loose, resulting in a decrease in later strength. An extreme ultra-high temperature resistant cement suitable for low and medium temperature cementing environments contains less C3AH6 than pure slurry cement paste, which reduces the later strength decline.

[0020] The fluid loss reducer is a solid composition obtained by mixing polyvinyl alcohol and sodium alginate in a mass ratio of 4-8:2-4. The polyvinyl alcohol is attached to the surface of cement particles to form a stable frame structure. The Na of sodium alginate + With Ca 2+ Ion exchange reaction occurs, and the cement stone accumulates to form a cross-linked network structure, thereby forming a hydrogel to fill the gaps and make the cement stone accumulate tightly.

[0021] The polyvinyl alcohol is a 17-88 type solid powder with a purity of more than 99.5%; the sodium alginate is an industrial-grade solid powder with a particle size of 80 to 100 meshes and a purity of more than 99.0%.

[0022] The retarder is prepared from a zwitterionic polymer AMSN retarder, boric acid and sodium glucoheptonate in a mass ratio of 2-3.5:1-2:1.5-2.0.

[0023] The mechanism of action of boric acid as a retarder is that it reacts with Ca in cement paste. 2+ The calcium borate precipitate is formed by the reaction, which covers the surface of the cement particles and forms a dense protective layer with low permeability, preventing the cement particles from exchanging substances with the outside world and delaying the cement hydration reaction.

[0023] The carboxyl group in sodium glucoheptonate can promote the formation of an acidic environment and delay the cement hydration reaction.

[0025] The monomers required for synthesizing the zwitterionic polymer retarder AMSN are: 2-acrylamido-2-methylpropanesulfonic acid (AMPS), maleic acid (MA), sodium p-styrenesulfonate (SSS) and cationic monomer (N, N-dimethyldodecyl ethyl methacrylate ammonium bromide).

[0026] The performance of polymers is generally determined by their molecular structure. Polymer retarders must be composed of polymer monomers with specific functional groups. In order to comprehensively exert the effects of various functional groups and form polymers with excellent retarding properties, it is first necessary to determine the polymer monomers involved in the reaction. According to the working conditions of unconventional oil and gas shallow thermal recovery wells, the optimization of polymer monomers mainly includes the following aspects:

[0027] (1) Slow down the hydration rate as much as possible and prolong the thickening time.

[0028] (2) Unconventional shallow wells are mostly within the range of 150 to 2000 m, with formation temperatures between 20 and 50 °C. Excessive retarding in low-temperature environments should be avoided.

[0029] (3) The negative impact on strength should be as small as possible, and there should be no significant weakening effect on other properties of the modified high-alumina cement slurry.

[0030] (4) It contains more hydrophilic and adsorption groups, ensuring good salt resistance and can be well compatible with other admixtures and additives.

[0031] (5) In the early stage of hydration, Al in the slurry 3+ The concentration is low, these small amounts of Al 3+ It may produce chelation with the retarding group, thus causing the "heart-wrapping" phenomenon during the thickening process of cement slurry. Introducing a cationic monomer, in a medium-low temperature environment, due to its hydrophobic association, it curls up and agglomerates, and the polymer retarder macromolecular chain will shrink, inhibiting the extension of the retarder molecules in the aqueous solution, thereby reducing the retarder molecules and the small amount of Al in the cement slurry in the early stage of hydration. 3+ The chelating effect produced avoids the occurrence of the "core" phenomenon during the thickening process.

[0032] The design principles of different functional groups on the side chain of AMSN retarder are:

[0033] (1) Introducing sulfonic acid groups to improve the temperature and salt resistance of synthetic polymers.

[0034] (2) To enhance the hydrolytic stability of the polymer retarder, amide groups are introduced.

[0035] (3) It has strong hydration and adsorption groups. By introducing reactive monomers containing carboxyl groups, the required adsorption groups come from this monomer, which is adsorbed on the surface of cement particles, limiting the exchange of substances with the outside world and reducing the cement hydration rate.

[0036] (4) Introducing benzene rings to reduce the negative impact on the compressive strength of cement paste.

[0037] (5) Introduce cationic monomers to avoid the occurrence of the "core" phenomenon and improve the stability of the slurry thickening process.

[0038] 2-Acrylamido-2-methylpropanesulfonic acid (AMPS) is a commonly used water-soluble anionic monomer. The sulfonic acid group it contains maintains strong resistance to external acid, alkali and salt erosion. The amide group also makes it have good hydrolysis stability and excellent thermal stability. The two groups work together to ensure the stability of the structure of the copolymerization product. Maleic acid (MA), as a reaction monomer containing a carboxyl group, increases the adsorption capacity of the zwitterionic polymer retarder molecular chain on cement particles, thereby hindering the hydration reaction of cement particles and prolonging the thickening time of high-alumina cement slurry. The benzene ring in the molecular structure of sodium styrene sulfonate (SSS) promotes excellent high temperature resistance and has a positive effect on the compressive strength of cement stone. The sulfonic acid group in the para position enhances the polymerization reaction induction effect and can improve the success rate of the polymerization reaction.

[0039] The synthesis process of the zwitterionic polymer AMSN retarder is as follows: monomers 2-acrylamido-2-methylpropanesulfonic acid (AMPS), maleic acid (MA), sodium p-styrenesulfonate (SSS) and cationic monomers (N, N-dimethyl dodecyl ethyl methacrylate ammonium bromide) are obtained by free radical copolymerization in 60-65° C. pure water by using azobisisobutylimidazoline hydrochloride initiator in a mass fraction ratio of 10-22:17-35:7.5-12:6.8-10, wherein the reaction pH is 4.0-4.5, and the reaction is performed for 3-5 hours to prepare a solution with a mass percentage concentration of 20-22%.

[0040] The toughening material is obtained by mixing basalt fiber and serpentine fiber in a mass ratio of 0.3-0.6:0.1-0.4. The basalt fiber is a golden brown long thin flaky solid with a length of 3-5 mm and a purity of more than 99.5%. It has the characteristic of high tensile strength and is suitable for mixing with cement materials to enhance cement performance and extend the life of buildings. It also has good high temperature resistance and toughening effect. The serpentine fiber is an off-white filamentous solid with a length of 3-5 mm and a purity of more than 99.0%. It is often used as a refractory material with good high temperature resistance. The serpentine fibers are mutually entangled in the cement stone structure, which greatly enhances the strength of the cement stone. The fiber is basically not affected by environmental factors, can alleviate the problem of cement stone strength shrinkage in the later stage, and improve the high temperature resistance of the cement stone.

[0041] The drag reducer is a liquid composition obtained by mixing a sulfonated aldehyde and ketone drag reducer and a polycarboxylic acid drag reducer in a mass ratio of 35-52:45-65. The sulfonated aldehyde and ketone drag reducer is a dark brown-red liquid prepared from acetone, sodium sulfite, formaldehyde, polyethylene glycol monoallyl ether and water, with a solid content of 35%; the polycarboxylic acid drag reducer type is a polyether with acrylic acid or methacrylic acid as the main chain and grafted with different side chain lengths, with a solid content of 20%.

[0042] The defoaming agent is a polyether-organosiloxane composite DF-E defoaming agent.

[0043] An operation process of an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment comprises the following steps:

[0044] The first step is to weigh the extreme ultra-high temperature resistant cementitious material, high temperature strength stabilizer, basalt fiber and serpentine fiber respectively according to mass.

[0045] The second step is to prepare the zwitterionic polymer retarder AMSN according to the steps, and then weigh boric acid and sodium glucoheptonic acid according to the mass ratio and mix them evenly to obtain a retarder suitable for an extreme ultra-high temperature cement slurry system resistant to low and medium temperature cementing environment.

[0046] The third step is to weigh polyvinyl alcohol and sodium alginate according to the mass ratio and mix them evenly to obtain a fluid loss reducer for an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments.

[0047] The fourth step is to weigh the defoaming agent and water according to the mass ratio.

[0048] Step 5: After the liquid and solid are mixed evenly, put the prepared liquid mixture into the slurry cup of the high-speed stirrer, and then put the solid mixture into the slurry cup. Stir at 4000 rpm for 15 seconds to allow the various substances to be fully contacted and mixed. Then adjust the speed to 12000 rpm and keep stirring at this speed for 35 seconds to obtain the final cement slurry. The density should be between 1.80 and 2.0 g / cm3 , that is, the above-mentioned extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The macroscopic structures of Example 1 and Comparative Example 1 dry-fired at 800°C are shown in Figure (a) for Example 1 and Figure (b) for Comparative Example 1. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described below in conjunction with embodiments and comparative examples. It should be noted that the following description is only for explaining the present invention and does not limit its content.

[0051] First, the sources of the materials used in the following examples and comparative examples are described:

[0052] CaO·Al2O3 was purchased from Henan Fengkai Refractory Material Co., Ltd.; 3Al2O3·2SiO2 was purchased from Merck Life Science Technology (Nantong) Co., Ltd.; CaSO4·2H2O was purchased from Shenzhen Hualei Gaodu Gypsum Co., Ltd.; NaAlO2 was purchased from Xi'an Wanlv Biotechnology Co., Ltd.; 2CaO·Al2O3·SiO2 was purchased from Merck Life Science Technology (Nantong) Co., Ltd.; Ca 10 (PO4)6(OH)2 was purchased from Xi'an Wanlv Biotechnology Co., Ltd.; Quartz sand was purchased from Hengyang Mineral Products Processing Plant in Lingshou County; Metakaolin was purchased from Shandong Qiyi Chemical Technology Co., Ltd.; Basalt fiber was purchased from Changzhou Bochao Engineering Materials Co., Ltd.; Serpentine fiber was purchased from Shijiazhuang Caishi Mineral Products Co., Ltd.; Polyvinyl alcohol was purchased from Guangzhou Ziyang Biotechnology Co., Ltd.; Sodium alginate was purchased from Jiangsu Tianshun Biotechnology Co., Ltd.; The zwitterionic polymer retarder AMSN was prepared by the laboratory of China University of Petroleum (East China); Boric acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Sodium glucoheptonate was purchased from Suzhou Zhengyang Chemical Technology Co., Ltd.; Polycarboxylic acid drag reducers were purchased from Shandong Yuncheng Huihuang New Building Materials Technology Co., Ltd.; DF-E defoamer was purchased from Chengdu OMEC Petroleum Technology Co., Ltd.

[0053] The specific experimental process is as follows:

[0054] Test method: According to GB / T 19139-2012 Oil Well Cement Test Method, SY / T 6544-2017 Oil Well Cement Slurry Performance Requirements, and SY / T 6466-2016 Oil Well Cement Stone Performance Test Method, the density, water loss, high and low temperature compressive strength, and thickening time of the cement slurry system were tested.

[0055] Embodiment 1

[0056] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0057] Prepare the cement slurry as follows: The first step is to weigh the extreme ultra-high temperature resistant cementitious material, high temperature strength stabilizer, basalt fiber and serpentine fiber respectively according to mass. The second step is to prepare the zwitterionic polymer retarder AMSN according to the steps, and then weigh boric acid and sodium glucoheptonic acid according to the mass ratio and mix them evenly to obtain a retarder suitable for an extreme ultra-high temperature cement slurry system resistant to low and medium temperature cementing environment. The third step is to weigh polyvinyl alcohol and sodium alginate according to the mass ratio and mix them evenly to obtain a fluid loss reducer for an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments. The fourth step is to weigh the defoaming agent and water according to the mass ratio. Step 5: After the liquid and solid are mixed evenly, put the prepared liquid mixture into the slurry cup of the high-speed stirrer, and then put the solid mixture into the slurry cup. Stir at 4000 rpm for 15 seconds to allow the various substances to be fully contacted and mixed. Then adjust the speed to 12000 rpm and keep stirring at this speed for 35 seconds to obtain the final cement slurry. The density should be between 1.80 and 2.0 g / cm 3 , that is, the above-mentioned extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment is obtained.

[0058] Embodiment 2

[0059] 100 parts of extreme high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 5.5 parts of ultra-high temperature retarder, including 2 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0060] The steps for preparing cement slurry are the same as those in Example 1.

[0061] Embodiment 3

[0062] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 6.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 1.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0063] The steps for preparing cement slurry are the same as those in Example 1.

[0064] Embodiment 4

[0065] 100 parts of extreme high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 9.5 parts of ultra-high temperature retarder, including 6 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0066] The steps for preparing cement slurry are the same as those in Example 1.

[0067] Embodiment 5

[0068] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 8.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 3.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0069] The steps for preparing cement slurry are the same as those in Example 1.

[0070] Embodiment 6

[0071] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 8.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 2 parts of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0072] The steps for preparing cement slurry are the same as those in Example 1.

[0073] Embodiment 7

[0075] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 6 parts of fluid loss reducer, including 4 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0076] The steps for preparing cement slurry are the same as those in Example 1.

[0077] Embodiment 8

[0078] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 4 parts of fluid loss reducer, including 2 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0079] The steps for preparing cement slurry are the same as those in Example 1.

[0080] Embodiment 9

[0081] 100 parts of extreme high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 9 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 3 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0082] The steps for preparing cement slurry are the same as those in Example 1.

[0083] Embodiment 10

[0084] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 10 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 4 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0085] The steps for preparing cement slurry are the same as those in Example 1.

[0086] Embodiment 11

[0087] 100 parts of extreme high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.8 parts of toughening materials, including 0.4 parts of basalt fiber, 0.4 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0088] The steps for preparing cement slurry are the same as those in Example 1.

[0089] Embodiment 12

[0090] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.4 parts of toughening materials, including 0.2 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0091] The steps for preparing cement slurry are the same as those in Example 1.

[0092] Comparative Example 1

[0093] 100 parts of pure aluminate cement, 28 parts of high temperature strength stabilizer, 0.6 parts of toughening material, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0094] The steps for preparing cement slurry are the same as those in Example 1.

[0095] Comparative Example 2

[0096] 100 parts of ordinary G-grade cement, 28 parts of high temperature strength stabilizer, 0.6 parts of toughening material, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0097] The steps for preparing cement slurry are the same as those in Example 1.

[0098] Comparative Example 3

[0099] 100 parts of extreme high temperature resistant cementitious materials, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0100] The steps for preparing cement slurry are the same as those in Example 1.

[0101] Comparative Example 4

[0102] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 2.5 parts of boric acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0103] The steps for preparing cement slurry are the same as those in Example 1.

[0104] Comparative Example 5

[0105] 100 parts of extreme high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0106] The steps for preparing cement slurry are the same as those in Example 1.

[0107] Comparative Example 6

[0108] 100 parts of extreme high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 4 parts of zwitterionic polymer retarder AMSN, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0109] The steps for preparing cement slurry are the same as those in Example 1.

[0110] Comparative Example 7

[0111] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 6 parts of polyvinyl alcohol, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0112] The steps for preparing cement slurry are the same as those in Example 1.

[0113] Comparative Example 8

[0114] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizers, 0.6 parts of toughening materials, including 0.4 parts of basalt fiber, 0.2 parts of serpentine fiber, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, and 41 parts of water. The water-to-solid ratio is 0.4.

[0115] The steps for preparing cement slurry are the same as those in Example 1.

[0116] Comparative Example 9

[0117] 100 parts of extremely high temperature resistant cementitious materials, 28 parts of high temperature strength stabilizer, 8 parts of fluid loss reducer, including 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 7.5 parts of ultra-high temperature retarder, including 4 parts of zwitterionic polymer retarder AMSN, 2.5 parts of boric acid, 1 part of sodium glucoheptonic acid, 1.5 parts of drag reducer, 5 parts of defoamer, 41 parts of water. The water-to-solid ratio is 0.4.

[0118] The steps for preparing cement slurry are the same as those in Example 1.

[0119] Performance test of extreme high temperature resistant cement slurry system suitable for low and medium temperature cementing environment

[0120] Table 1 Performance of extremely high temperature resistant cement slurry suitable for low and medium temperature cementing environment

[0121] As shown in Table 1, the cement slurry system of Example 1 has moderate density, good fluidity, and a smooth thickening process. There is no abnormal gelling, "core wrapping" and other phenomena. At the same time, the right-angle thickening phenomenon is obvious, and the API water loss is less than 50 mL, which meets the API water loss standard. In general, the extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment of the present invention meets the requirements of on-site use.

[0122] It can be seen from Table 1 that the thickening time of the cement slurries of Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 4, 5 and 6 at 40°C and 0.1 MPa is 327min, 213min, 245min, 271min, 278min, 293min, 78min, 150min and 178min, respectively. The ultra-high temperature retarder obtained by compounding according to the ratio of 4 parts of AMSN, 2.5 parts of boric acid and 1 part of sodium glucoheptonic acid has the best retarding effect. The thickening time of an extreme ultra-high temperature resistant cement slurry suitable for low and medium temperature cementing environment is 327min, which fully meets the cementing construction requirements in terms of thickening time index; the thickening process is stable, the right-angle thickening is obvious, and no abnormal phenomenon occurs.

[0123] After adding boric acid retarder in comparative example 4, the thickening time of the study is extended with the increase of boric acid addition. However, if the amount of boric acid added is further increased to achieve the purpose of extending the thickening time, the slurry will show "super slow setting" phenomenon, and effective strength cannot be formed after curing for 1 day. Even the solidified cement stone has a loose structure and poor thermal shock resistance, and cannot form high strength. Boric acid is applied to an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment. The slow setting effect is limited, and the thickening process is unstable. Large addition has a great impact on strength, and the overall performance is poor. Therefore, it is not suitable to be used alone as a retarder for an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment.

[0124] After adding sodium glucoheptonic acid retarder in comparative example 5, a "bulge" appeared in the thickening curve, and a circle of gelling material was wrapped around the slurry axis, that is, the cement slurry thickening process had a "core" phenomenon, which may be related to the high content of alumina in the slurry, forming insoluble metal-organic complexes, which were intertwined with other hydration products, resulting in abnormal gelling. During on-site cementing construction, abnormally gelled cement slurry is easy to block the pumping channel within a width of less than 10 cm, hindering the injection of cement slurry and causing huge safety hazards to cementing operations.

[0125] After adding the zwitterionic polymer retarder AMSN in Comparative Example 6, the thickening time of an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments was further extended. When the addition amount reached 4%, the thickening time could be increased to 173 minutes, and no "core" phenomenon occurred. However, the consistency change during the thickening process of the slurry showed instability, and the right-angle thickening performance was poor.

[0126] Although the effect of adding zwitterionic polymer retarder AMSN is good, it should not be added too much, which will easily cause a decrease in strength. The cement paste with 3d curing has the largest strength decrease, and the medium and long-term strength decrease is reduced. This is because the retarder slows down the early hydration rate of modified high-alumina cement, thereby inhibiting the development of early strength of cement paste, resulting in a large decrease in strength. However, as the curing time increases, the cement paste gradually hydrates completely. Therefore, as the curing time is extended, the retarder's effect on reducing strength is also weakened.

[0127] As can be seen from Table 1, the API water loss of an extreme ultra-high temperature resistant cement slurry system suitable for a low and medium temperature cementing environment in Examples 1, 7, 8, 9, 10 and Comparative Examples 7 and 8 is 40 mL, 61 mL, 69 mL, 59 mL, 63 mL, 113 mL, and 117 mL. Polyvinyl alcohol cannot control the water loss of the slurry when the dosage is small. When the dosage is 6%, the water loss of the cement slurry is controlled to a certain extent, but the relevant cementing water loss performance requirements are not met. The water loss control effect of polyvinyl alcohol is general; sodium alginate has a certain control effect on the water loss of an extreme ultra-high temperature resistant cement slurry system suitable for a low and medium temperature cementing environment, but the water loss is still large, and the relevant cementing water loss performance requirements are still not met. After increasing the dosage, the improvement of its water loss control effect is limited.

[0129] In embodiments 1, 7, 8, 9 and 10, polyvinyl alcohol and sodium alginate, which have a certain water loss control effect, are selected to form a compounded fluid loss reducer, in order to solve the problem of water loss control of a modified ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments through compounding.

[0130] When polyvinyl alcohol and sodium alginate are mixed in different proportions, the water loss decreases with the increase of the sodium alginate addition ratio. The comparison shows that the water loss control effect of sodium alginate is better than that of polyvinyl alcohol. The API water loss of 6% polyvinyl alcohol + 2% sodium alginate is 40mL, which is the lowest level of water loss in all mixed proportions. When 6% polyvinyl alcohol + 2% sodium alginate is mixed, polyvinyl alcohol adheres to the surface of cement particles to form a stable structure. + With Ca 2+ An ion exchange reaction occurs, and the particles accumulate to form a cross-linked network structure, thereby forming a hydrogel to fill the voids and obtain a low permeability filter cake. Through the combined action of the two fluid loss reducers, the API water loss of the slurry is less than 50 mL, achieving the goal of controlling water loss.

[0131] Performance test of cement stone resistant to extreme ultra-high temperature in low and medium temperature cementing environment

[0132] The strength of cement paste under medium and low temperature curing environment is shown in Table 2.

[0133] Table 2 Cement paste strength under low temperature curing environment

[0134] It can be seen from Table 2 that the compressive strength of cement paste in all embodiments is above 50 MPa. Taking Example 1 of 40°C low temperature curing environment as an example, the compressive strength reaches 58.91 MPa at 1d, and the high compressive strength is formed quickly. The compressive strength reaches a peak value of 68.47 MPa at 14d, and the compressive strength remains at 52.88 MPa at 200d, which is 24.73% lower than the peak compressive strength, but still remains at a relatively high level. The compressive strength of an extreme ultra-high temperature resistant cement paste suitable for low and medium temperature cementing environment under low temperature environment does not decline significantly.

[0135] Comparative Example 1 uses pure aluminate cement, the overall strength of the cement paste is low, and the strength declines seriously in the later stage; Comparative Example 2 uses ordinary G-grade cement, the strength declines slowly, but the early strength increases slowly under the low-temperature curing environment, and the cement paste has low initial strength; Comparative Example 3 has serious strength decline in the later stage; Comparative Examples 4, 5, 6, 7, and 8 have poor cement slurry thickening and water loss properties, which affects the strength of the cement paste. The initial strength of the cement paste is lower than that of the embodiment, and the long-term strength declines seriously; Comparative Example 9 does not add toughening materials, the cement paste has low initial strength, and the long-term strength declines seriously.

[0136] The strength of cement paste under high temperature and extreme ultra-high temperature curing environment is shown in Table 3.

[0137] Table 3 Cement paste strength under high temperature and extreme ultra-high temperature curing environment

[0138] It can be seen from Table 3 that under the high-temperature curing environment of 315°C, the strength of cement paste in all embodiments is maintained at a relatively high level, and the strength of cement paste cured at a lower temperature decreases less. Taking Example 1 as an example, the compressive strength of cement paste reaches 61.52MPa after 7 days, which is 7.22MPa lower than that of cement paste cured in a low-temperature environment of 40°C. The problem of cement paste compressive strength decay is not obvious under high-temperature environment. Taking the ultra-high-temperature curing environment of 800°C as an example, the strength decreases by 13.03MPa after the first round of dry burning, but after the first round, the compressive strength of cement paste in the second and third rounds of dry burning decreases very little, and the high-temperature resistance of cement paste is significantly improved. At the same time, the problem of high-temperature cracking of cement paste is alleviated to a great extent.

[0139] Through microscopic analysis, it is found that an extreme ultra-high temperature resistant cement paste suitable for low and medium temperature cementing environment has a tight microstructure, generates C2ASH8, limits the conversion of hydration products to C3AH6, thereby reducing the strength decay rate, generates Ca3Al2(SiO4)3 at high temperature, promotes the improvement of internal structure density, and enhances high temperature strength.

[0140] It can be seen from Table 3 that under high temperature or extremely high temperature curing environment, the strength of the cement paste in Comparative Example 1 is relatively small. After extremely high temperature curing, the macroscopic cracking of the cement paste is obvious, the microstructure is severely damaged, and the strength of the cement paste is seriously decayed, which is different from the macroscopic structure of Example 1. Figure 1 As shown; in comparative example 2, the strength of cement paste declines slowly, but the initial strength increases slowly; in comparative example 3, there is a lack of high temperature strength stabilizer, and the strength of cement paste declines seriously under high temperature environment; in comparative example 9, there is a lack of toughening material, and the compressive strength of cement paste is significantly lower than that of embodiment 1, and the high temperature cracking problem of cement paste is only alleviated to a small extent.

[0141] The elastic modulus of cement paste under different curing conditions is shown in Table 4. The elastic modulus of Example 1 is relatively small, which meets the toughness requirements of cement paste while maintaining a relatively high strength level of cement paste.

[0142] Table 4 Elastic modulus of cement paste under different curing conditions (taking 40℃, 315℃, 800℃ as examples)

[0143] The toughening material used in the extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment of the present invention is obtained by mixing basalt fiber and serpentine fiber in a mass ratio of 0.3-0.6:0.1-0.4. The two fibers can not only increase the elastic toughness of cement stone, but also have good high temperature resistance. Basalt fiber has the characteristics of high tensile strength, which is suitable for mixing with cement materials to enhance cement performance and extend the service life of cement stone. It has a wide operating temperature range and good high temperature resistance. Serpentine fibers are intertwined with each other in the cement stone structure, which greatly enhances the strength of the extreme ultra-high temperature resistant cement stone suitable for low and medium temperature cementing environment. The fiber is basically not affected by environmental factors, and is often used as a refractory material with good high temperature resistance. At the same time, it alleviates the problem of cement stone strength shrinkage in the later stage.

[0144] The above is only a preferred specific implementation of the present invention, but the present invention is not limited to the examples listed. Similar effects can be obtained in other embodiments by using the relevant materials and the method mechanism in the present invention. Therefore, for those skilled in the art, without departing from the principles and spirit of the present invention, the improvements made are all within the scope of protection of the claims of the present invention.

Claims

1. A material composition and application of an extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environments, characterized in that: In parts by weight, the composition ratio of each component is 100 parts of extreme ultra-high temperature resistant cementitious material, 25-33 parts of high temperature strength stabilizer, 2-8 parts of retarder, 6-10 parts of fluid loss reducer, 0.4-1.0 parts of toughening material, 1.0-1.8 parts of drag reducer, 0.3-0.6 parts of defoamer, and 35-48 parts of water; An extremely high temperature resistant cement slurry system suitable for low and medium temperature cementing environment, wherein the extremely high temperature resistant cement gelling material is CaO·Al2O3, 3Al2O3·2SiO2, CaSO4·2H2O, NaAlO2, 2CaO·Al2O3·SiO2, Ca 10 The solid composite obtained by mixing (PO4)6(OH)2 in a mass ratio of 36-42:8-13:23-29:6-10:12-15:8-15 has a fast hydration rate of CaO·Al2O3 in the early stage, which improves the early strength. CaSO4·2H2O and NaAlO2 promote the formation of hydration products ettringite and hydrated calcium aluminosilicate gel, which promotes the strength development of extremely high temperature resistant cementitious materials. Under high temperature environment, 3Al2O3·2SiO2 and 2CaO·Al2O3·SiO2 promote the hydration products to further form structurally stable hydrated calcium aluminum feldspar C2ASH8 and calcium aluminum garnet Ca3Al2(SiO4)3, so that the ultra-high temperature resistant cementitious materials maintain long-term strength stability. 10 (PO4)6(OH)2 plays a strong binding role in the hydration process, promoting the cementitious material to maintain stable strength under extreme ultra-high temperature conditions, and can reduce the complexation of phosphorus and calcium ions in the hydration process, so that the cement slurry system has better fluidity and reasonable thickening time; An extreme and ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment, wherein the CaO·Al2O3 in the extreme and ultra-high temperature resistant cement gelling material is a powdered solid with a mesh size of 50-80 meshes and a purity of more than 98.0%; 3Al2O3·2SiO2 is an industrial-grade solid powder with a particle size of 200-240 meshes and a purity of more than 99.0%; Al2O3 is an industrial-grade solid powder with a particle size of 325-400 meshes and a purity of more than 99.5%; NaAlO2 is an industrial-grade solid powder with a particle size of 160-240 meshes and a purity of more than 98.5%; 2CaO·Al2O3·SiO2 is an industrial-grade solid powder with a particle size of 200-240 meshes and a purity of more than 99.5%; Ca 10 (PO4)6(OH)2 is an industrial grade solid powder with a particle size of 900-1250 mesh and a purity of more than 99.8%; An extreme ultra-high temperature resistant cement slurry system suitable for low and medium temperature cementing environment, wherein the high temperature resistant strength stabilizer is a solid composition obtained by mixing metakaolin and quartz sand in a mass ratio of 17-23:9-14, and the high temperature resistant strength stabilizer provides highly active silicon dioxide and aluminum oxide to form aluminosilicate minerals under high temperature conditions, which has good extreme ultra-high temperature resistance effect; wherein the metakaolin is an industrial grade solid powder with a particle size of 900-1250 meshes and a purity of more than 99.0%; the quartz sand is an industrial grade solid powder with a particle size of 150-240 meshes and a purity of more than 99.5%; The invention discloses an extremely high temperature resistant cement slurry system suitable for low and medium temperature cementing environment, wherein the retarder is a composite solution obtained by mixing a zwitterionic polymer AMSN retarder, boric acid and sodium glucoheptonic acid in a mass ratio of 3 to 5.5:1 to 3:1.0 to 2.0, wherein the zwitterionic polymer retarder AMSN is composed of monomers 2-acrylamido-2-methylpropanesulfonic acid (AMPS), maleic acid (MA), sodium p-styrenesulfonate (SSS) and a cationic monomer (N, N-dimethyldodecylmethyl Acrylate ethyl ammonium bromide) is obtained by free radical copolymerization in pure water at 60-65°C with azobisisobutylimidazoline hydrochloride as an initiator in a mass fraction ratio of 10-22:17-35:7.5-12:6.8-10, wherein the reaction pH is 4.0-4.5, and the reaction is performed for 3-5 hours to prepare a solution with a mass percentage concentration of 20-22%; boric acid is an industrial grade solid powder with a purity of more than 99.5%; sodium glucoheptonic acid is an industrial grade solid powder with a purity of more than 98.0%; An extremely high temperature resistant cement slurry system suitable for low and medium temperature cementing environments, wherein the fluid loss reducer is a solid composition obtained by mixing polyvinyl alcohol and sodium alginate in a mass ratio of 4 to 8:2 to 4, the polyvinyl alcohol is attached to the surface of cement particles to form a stable frame structure, and the Na content of sodium alginate is 2.5-3.

5. + With Ca 2+ An ion exchange reaction occurs, and a cross-linked network structure is formed by stacking, thereby forming a hydrogel to fill the gaps and obtain a low permeability filter cake; wherein the polyvinyl alcohol is a 17-88 type solid powder with a purity of more than 99.5%; the sodium alginate is an industrial grade solid powder with a particle size of 80-100 meshes and a purity of more than 99.0%; The invention discloses an extremely high temperature resistant cement slurry system suitable for low and medium temperature cementing environment, wherein the toughening material is a solid composition obtained by mixing basalt fiber and serpentine fiber in a mass ratio of 0.3-0.6:0.1-0.4, and the toughening material can not only form a bridge in the cement stone to improve its strength and toughness, but also has a certain high temperature resistance effect; wherein the basalt fiber has a length of 3-5 mm and a purity of more than 99.5%; the serpentine fiber has a length of 3-5 mm and a purity of more than 99.0%.

2. The extreme high temperature resistant cement slurry system suitable for low and medium temperature cementing environment according to claim 1, characterized in that The drag reducer is a liquid composition obtained by mixing a sulfonated aldehyde ketone drag reducer and a polycarboxylic acid drag reducer in a mass ratio of 35-52:45-65.

3. The extreme high temperature resistant cement slurry system suitable for low and medium temperature cementing environment according to claim 1, characterized in that The defoamer is a polyether-organosiloxane composite DF-E defoamer, and the water is fresh water or low-mineralization water.

Citation Information

Patent Citations

  • High-temperature-resistant non-silicate cement paste system for cementing thermal production well of thickened oil

    CN102994058A

  • High-strength high-toughness high-temperature-resistant oil well cement slurry system as well as preparation method and design method thereof

    CN106833567A

  • Well cementation material suitable for low-temperature environment and production method of well cementation material

    CN110105030A

  • Long-term high-temperature-resistant toughened well-cementing sand-added cement composite material and preparation method thereof

    CN114477876A

  • Non-declining thick oil thermal recovery cement paste resistant to high temperature of 350 DEG C

    CN115231869A